FAKTOR KEBERHASILAN PROGRAM SILASIDAKEP DALAM PEMBUATAN AKTA KELAHIRAN DI KABUPATEN SUMEDANG - Dhesti widya Nurhasanah Ningrum; Denisya Ramadhanti; Ega Nugraha; Ineu Wulandari; Muhaimin Abdur Razzak; Silfa Fauziyyah (FISIP Universitas Sebelas April, 2022)
The Silasidakep program in the issuance of birth certificates is one of the innovation programs that aims to form birth certificates, namely as a form of state recognition of a person's existence before the law. In addition, birth certificates are also useful for applying for jobs, requirements for making ID cards and family cards, school entry requirements, marriage requirements, passport processing, voting rights, and inheritance rights management. So it can be concluded that the birth certificate is one of the important documents that must be owned by everyone. Silasidakep is an online service program provided to the public to make it easier to make a Birth Certificate by simply accessing the Silidakep application. Success factors are very important to provide studies and input in determining programs to achieve targets. This research uses qualitative method with descriptive analysis type. Informants were determined using purposive sampling technique so that the informants in this study were the Head of the Civil Registry Service, Head of the Birth Certificate Section, Birth and Death Certificate Administration, Birth and Death Section, Civil Registration Service and Operators. Civil Registration Service. Then the data collection technique is done by literature study, field study (observation, interviews and documentation), and triangulation. After that, data processing uses data reduction, data presentation, conclusion drawing/data verification. The Silasidakep program in making birth certificates at the Population and Civil Registration Office of Sumedang Regency has been implemented quite well, although there are some things that need to be improved. Based on the results of the research, there are several suggestions, among others, it is necessary to make a special budget for the Silasidakep program or in the issuance of a Birth Certificate without having to adjust to the general budget used as it is today and provide a wider and adequate document archiving space.